PENGARUH FINANCIAL LITERACY, FINANCIAL WELL-BEING, FINANCIAL ATTITUDE, TERHADAP RETIREMENT PLANNING DIMODERASI OLEH HERDING BEHAVIOUR PADA PEKERJA KONSTRUKSI - Erni Erni; Abdurrahman Abdurrahman (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2026)
This study examines the influence of Financial Literacy, Financial Well-Being, and Financial Attitude on Retirement Planning, with Herding Behavior as a moderating variable. This study aims to explore how personal financial factors influence the readiness of construction workers in planning for retirement in Pekanbaru City, Indonesia. Using a quantitative approach, data was collected through an online survey from 200 respondents who were employees of four construction service companies, namely PT Buana Global Mandiri, PT Hutama Karya Infrastruktur, PT Wira Agung, and PT Andalan Tunas Mandiri. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results show that Financial Literacy, Financial Well-Being, and Financial Attitude have a positive and significant influence on Retirement Planning. In addition, Herding Behavior is proven to moderate the relationship between Financial Literacy and Retirement Planning. This study highlights the importance of improving financial knowledge and managing financial attitudes for construction workers to be better prepared for retirement. These results also provide insights for construction companies, financial planners, and policymakers to design strategies that encourage better retirement planning in the construction sector.